2006
DOI: 10.1021/ef0602574
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Energy Recuperation on the Efficiency of a Solid Oxide Fuel Cell Power System

Abstract: In this paper, the influence of energy recuperation on the efficiency of a solid oxide fuel cell (SOFC) power system is studied with the GCTool software developed by the American Argonne National Laboratory (ANL). The recuperative energies include partial recycled air exhausted from cathode side, recirculated fuel and steam from the anode side of the SOFC, and combustion gases from anode exhaust, individually. The methane is chosen as fuel, air is oxidant, and the pressure drops due to streams transported thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Santangelo and Tartarini [4] compared the fuel consumption characteristics of fuel cells and traditional power generation systems and suggested that fuel cell devices provided the potential for developing CHP systems for residential and industrial applications with virtually complete energetic independence. Chung et al [5,6] investigated the effects of energy recuperation on the efficiency of a SOFC and showed that the overall system efficiency could be increased from 50% to 68% by recirculating the partial fuel and steam from the anode exhaust of the SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…Santangelo and Tartarini [4] compared the fuel consumption characteristics of fuel cells and traditional power generation systems and suggested that fuel cell devices provided the potential for developing CHP systems for residential and industrial applications with virtually complete energetic independence. Chung et al [5,6] investigated the effects of energy recuperation on the efficiency of a SOFC and showed that the overall system efficiency could be increased from 50% to 68% by recirculating the partial fuel and steam from the anode exhaust of the SOFC.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the system's performance varied significantly under different modes, with the homogeneous charge compression ignition (HCCI) mode yielding the best results. Chung and colleagues investigated the impact of energy recovery on SOFC efficiency [151]. They supplied the high-temperature unreformed fuel directly from the SOFC to the afterburner and improved overall system efficiency from 50% to 68% by partially combusting anode exhaust gas and recycling steam.…”
Section: Waste Heat Recoverymentioning
confidence: 99%
“…Several researchers proposed both the mechanical design and catalytic combustion burners. , In addition to burner design, studies on SOFC process design considering the afterburner influence were also conducted. For example, Chung et al investigated the benefits of fuel recirculation using an afterburner, and their results showed that recirculating partial fuel and steam from anode-off-gas can increase the overall system efficiency by around 36% . Moreover, several simulation studies analyzed dynamic correlations among the afterburner, stack, heat exchanger, and reformer and explored optimal operation ways of the SOFC system with an afterburner. …”
Section: Introductionmentioning
confidence: 99%